Resistivity Measurements on Bulk Bi 2 Sr 2 CaCu 2 O 8+δ : Contribution of Vortices at Low Magnetic Fields - de la Cruz, Clarina; Guerra, Leandro; Sarmago, Roland; Salvador, Arnel (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The behavior of high-temperature superconductors in the presence of an external magnetic field is of particular interest in light of its technological application and commercialization. In this paper, we performed resistivity measurements on bulk superconducting pellets of Bi 2 Sr 2 CaCu 2 O 8+δ in the presence of external magnetic fields below 0.5T. The broadening of the transition region below Tc in the resistivity plots, was attributed to the residual resistance imparted by flux flow in the sample. From I-V measurements at 50 K at fields below 0.6T, the contribution of vortices was quantitatively measured as a flux flow resistivity which range from 0.1231 to 1.700 (m(-mm) for applied magnetic fields from 0.04T to 0.6T. The increase in the flux flow resistivity with increasing applied field was due to the increase in the number of vortices moving in steady state motion brought about by the interaction of the vortices with the transport current.
Keywords: superconductors; resistivity; vortices; flux flow resistivity; magnetoresistance